Surgical treatment of a patient with multiple endocrine neoplasia type 2A - T. A. Britvin; E. V. Bondarenko; A. V. Krivosheev; O. A. Nechaeva; T. S. Tamazyan; D. V. Podrez; L. E. Gurevich; P. A. Korosteleva (Вестник хирургии имени И.И. Грекова)
The diagnosis and treatment of multiple endocrine neoplasia type 2A syndrome or Sipple’s syndrome, as well as other endocrine hereditary syndromes, presents certain difficulties for several reasons. One of them is the rarity of this pathology and, as a result, the lack of awareness of physicians. In addition, the diagnosis requires a comprehensive examination and a high level of clinical, laboratory, radiation and morphological diagnostics. And finally, surgical treatment, which is essentially the only method, involves an individual approach to each patient. We present the clinical case of Sipple's syndrome in a 39-year-old man. The diagnosis was carried out of medical history, clinical examination, laboratory tests (24-hour urine excretion of metanephrines and normetanephrines; serum calcium, calcitonin and parathyroid hormone levels), neck ultrasound and abdominal CT scan and was confirmed by histopathological examination and genetic testing for RET mutation. The achievement of the endpoint in the form of normalization of blood pressure and the absence of adrenal insufficiency was due to radical surgical treatment.